2021
DOI: 10.3892/br.2021.1405
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resection for pelvic retroperitoneal Castleman's disease: A case report and review literature

Abstract: Castleman's disease (CD) is a rare atypical lymphoproliferation disorder first reported in 1954. Clinically, CD is classified as unicentric or multicentric CD based on anatomical distribution. Unicentric CD primarily affects the mediastinum, and rarely affects the retroperitoneal location. The standard treatment for unicentric CD is complete surgical resection; however, this can be complicated by a high degree of attachment with other organs or hypervascularity. Preoperative angiography and embolization of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Given their proximity to major vascular structures of the pelvis, surgeons were occasionally faced with a clinical situation in which a large-volume blood transfusion was necessary (8). Thus, certain surgeons used preoperative angiography and embolization of the feeding arteries to the tumor in order to prevent or limit intraoperative bleeding (9). The present study reported a rare case of UCD located in the pelvic retroperitoneum, which was completely resected by meticulous laparoscopic surgery with limited bleeding.…”
Section: Introductionmentioning
confidence: 84%
“…Given their proximity to major vascular structures of the pelvis, surgeons were occasionally faced with a clinical situation in which a large-volume blood transfusion was necessary (8). Thus, certain surgeons used preoperative angiography and embolization of the feeding arteries to the tumor in order to prevent or limit intraoperative bleeding (9). The present study reported a rare case of UCD located in the pelvic retroperitoneum, which was completely resected by meticulous laparoscopic surgery with limited bleeding.…”
Section: Introductionmentioning
confidence: 84%
“…Finally, our results also show significant upregulation of the key neurogenic factor neurexin‐1α, which influences synapse function and neuronal connectivity, [ 239,240 ] with major downregulation of SIRPα, expressed on myeloid cells and neurons. [ 241,242 ] Further, KLKB1, a blood coagulation factor, [ 243 ] was also significantly upregulated in P7C3 treated animals. Although their effect, in addition to the neurotrophin, TrkA is evidently significant in this study, it remains unclear how osteoneuronal activity contributed to the protection in bone loss, and maintenance in bone strength observed following OVX.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes in the reported cases, such as estimated blood loss, effect on tumor size, time interval between angioembolization and surgery, postoperative complications, and use of a surgical drain have been reported. Table 1 lists the literature review on the role of preoperative angioembolization in CD [16] , [17] , [18] , [19] , [20] , [21] .…”
Section: Clinical Discussionmentioning
confidence: 99%